2006
DOI: 10.1038/sj.cdd.4402031
|View full text |Cite
|
Sign up to set email alerts
|

XLX is an IAP family member regulated by phosphorylation during meiosis

Abstract: The balance between proliferation and cell death is critical for embryonic development and adult tissue homeostasis. Within an individual cell, coordination of these pathways is aided by direct communication between cell cycle factors and molecules that regulate apoptosis. Here, we show that XLX, a Xenopus laevis inhibitor of apoptosis (IAP) family member, exhibits characteristics typical of an IAP, such as caspase inhibition and autoubiquitylation. However, unlike other IAPs described thus far, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…GVBD results in a sharply demarcated loss of pigment in the animal pole, which, although distinct from apoptotic morphology, renders visual determination of whether a meiotic oocyte (post-GVBD) is undergoing apoptotic death challenging (Figure 5a). Using cell-free systems, we and others have reported that a meiotic state (M-phase) engenders resistance to cytochrome c -induced caspase activation24,25. A comparison of IRDye fluorescence in immature and mature (post-GVBD) oocytes microinjected with cytochrome c confirmed that sensitivity to cytochrome c decreases with maturation (Figure 5b).…”
Section: Resultssupporting
confidence: 57%
“…GVBD results in a sharply demarcated loss of pigment in the animal pole, which, although distinct from apoptotic morphology, renders visual determination of whether a meiotic oocyte (post-GVBD) is undergoing apoptotic death challenging (Figure 5a). Using cell-free systems, we and others have reported that a meiotic state (M-phase) engenders resistance to cytochrome c -induced caspase activation24,25. A comparison of IRDye fluorescence in immature and mature (post-GVBD) oocytes microinjected with cytochrome c confirmed that sensitivity to cytochrome c decreases with maturation (Figure 5b).…”
Section: Resultssupporting
confidence: 57%
“…Among the other apoptotic factors, the inhibitor of apoptosis (IAP) family of proteins containing the highly conserved baculoviral IAP repeat (BIR) are known to inhibit apoptosis, in some cases, through direct binding of caspases. XLX and XIAP, the X. laevis BIR family proteins, have been shown to inhibit the apoptotic process in the cell-free system of X. laevis egg extract [102, 103]. However, their involvement in metamorphosis as well as TH dependency remains to be determined.…”
Section: Apoptotic Factors Regulated By Thmentioning
confidence: 99%
“…4, 6XHis-xE-IAP). These results indicate that the stabilized xXIAP and xEIAP/XLX could also contribute to the inhibition of apoptosis in acid-treated egg extracts [18,19]. Altogether, multiple apoptosis-regulating pathways were affected by the addition of acidic solutions to egg extracts.…”
Section: Resultsmentioning
confidence: 81%